2008
DOI: 10.2147/btt.s2372
|View full text |Cite
|
Sign up to set email alerts
|

Colon-targeted delivery of live bacterial cell biotherapeutics including microencapsulated live bacterial cells

Abstract: There has been an ample interest in delivery of therapeutic molecules using live cells. Oral delivery has been stipulated as best way to deliver live cells to humans for therapy. Colon, in particular, is a part of gastrointestinal (GI) tract that has been proposed to be an oral targeted site. The main objective of these oral therapy procedures is to deliver live cells not only to treat diseases like colorectal cancer, inflammatory bowel disease, and other GI tract diseases like intestinal obstruction and gastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 228 publications
(192 reference statements)
0
6
0
1
Order By: Relevance
“…Colitis was induced by the method of [31] with slight modifications. Except the animals in normal control group, all the other animals were supplemented with 3% DSS in drinking water throughout the experimental period.…”
Section: Induction Of Colitis and Treatmentmentioning
confidence: 99%
“…Colitis was induced by the method of [31] with slight modifications. Except the animals in normal control group, all the other animals were supplemented with 3% DSS in drinking water throughout the experimental period.…”
Section: Induction Of Colitis and Treatmentmentioning
confidence: 99%
“…With regard to CRC, numerous clinical trials have shown the potential of probiotics as adjuvants, reducing the side effects associated with chemotherapy and surgeries in CRC-patients [85,86]. The delivery of live biotherapeutic cells for the treatment of GI diseases is well known and the immunomodulatory and anti-inflammatory properties of probiotics on colon cancer is well understood [87]; however, few studies exist that demonstrate the potential of probiotics to eradicate CRC-associated bacteria from the gut microbiome, consequently reducing the risk of disease development.…”
Section: Potential Use Of Biotherapeutic Bacteria To Target Colorectamentioning
confidence: 99%
“…The enzymes they produce areglucuronidase, -galactosidase, nitroreductase, azoreductase, etc. Number of mucosal bacteria increases progressively in the state of inflammation, with concentrations relatively higher in patients with active disease (Prakash & Urbanska, 2008).…”
Section: Colon As a Target For Drug And Probiotic Cell Delivery In Comentioning
confidence: 99%